Answer:
[tex] \frac{dy}{dx} = - \frac{ {x}^{3} }{ {y}^{3} } [/tex]
Step-by-step explanation:
Differentiate both sides of the equation (consider y as a function of x).
[tex] \frac{d}{dx} ( {x}^{4} + {y}^{4} (x)) = \frac{d}{dx} (16)[/tex]
the derivative of a sum/difference is the sum/difference of derivatives.
[tex]( \frac{d}{dx} ( {x}^{4} + {y}^{4} (x))[/tex]
[tex] = ( \frac{d}{dx} ( {x}^{4} ) + \frac{d}{dx} ( {y}^{4} (x)))[/tex]
the function of y^4(x) is the composition of f(g(x)) of the two functions.
the chain rule:
[tex] \frac{d}{dx} (f(g(x))) = \frac{d}{du} (f(u)) \frac{d}{dx} (g(x))[/tex]
[tex] = ( \frac{d}{du} ( {u}^{4} ) \frac{d}{dx} (y(x))) + \frac{d}{dx} ( {x}^{4} )[/tex]
apply the power rule:
[tex](4 {u}^{3} ) \frac{d}{dx} (y(x)) + \frac{d}{dx} ( {x}^{4} )[/tex]
return to the old variable:
[tex]4(y(x) {)}^{3} \frac{d}{dx} (y(x)) + \frac{d}{dx} ( {x}^{4} )[/tex]
apply the power rule once again:
[tex]4 {y}^{3} (x) \frac{d}{dx} (y(x)) + (4 {x}^{3} )[/tex]
simplify:
[tex]4 {x}^{3} + 4 {y}^{3} (x) \frac{d}{dx} (y(x))[/tex]
[tex] = 4( {x}^{3} + {y}^{3} (x) \frac{d}{dx} (y(x)))[/tex]
[tex] = \frac{d}{dx} ( {x}^{4} + {y}^{4} ))[/tex]
[tex] = 4( {x}^{3} + {y}^{3} (x) \frac{d}{dx}(y(x))) [/tex]
differentiate the equation:
[tex]( \frac{d}{dx} (16)) = (0)[/tex]
[tex] = \frac{d}{dx} (16) = 0[/tex]
derivative:
[tex]4 {x}^{3} + 4 {y}^{3} \frac{dy}{dx} = 0[/tex]
[tex] \frac{dy}{dx} = - \frac{ {x}^{3} }{ {y}^{3} } [/tex]